Gamified Learning: Evaluating the Impact of Duolingo on Language Retention and Academic Performance in Secondary School Students - Herni Sri Wulandari; Halim, Abdul (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
The study investigates the relationship between Duolingo usage language learning retention, and academic achievements among high school students. Duolingo, it is known for its user-friendly interface and gamified learning approach, has acquired popularity in the field of language instruction. The major goal of this study is to determine if Duolingo usage improves academic achievement and language retention in secondary school students. This study lasted four months and involved 40 students from SMA Istiqamah Muhammadiyah Samarinda. The collection of data includes Duolingo achievement assessments and questionnaires indicated to assess patterns of Duolingo usage, language retention, and app satisfaction. Statistical analysis, specifically the Pearson correlation coefficient, was employed to assess the level and course of the correlation between Duolingo use and language learning results. The findings indicate a significant positive correlation between the use of Duolingo and the retention of language learning, as well as an improvement in academic achievements. The results suggest that integrating Duolingo into the language learning curriculum is beneficial for students, enhancing both their engagement and learning outcomes. Furthermore, the study highlights the need for further research to explore the specific mechanisms through which Duolingo impacts language learning and to expand the findings to larger and more diverse student populations. This research contributes valuable insights for educators and policymakers seeking to incorporate digital learning tools into language education and underscores the potential of Duolingo as an effective supplementary resource for language learning in secondary schools.